Solar Light Elimination of Bacteria, Yeast and Organic Pollutants by Effective Photocatalysts Based on Ag/Cr-TiO2 and Pd/Cr-TiO2 - Mónica Hernández-Laverde; Nicola Morante; Blanca Liliana Gutiérrez; Julie Joseane Murcia; Katia Monzillo; Diana Sannino; Vincenzo Vaiano (Nanomaterials)
This study focused on searching for more effective nanomaterials for environmental remediation and health protection; thus, coliform bacteria, yeast and the organic food dye sunset yellow were selected as target pollutants to be eliminated under solar light by Ag/Cr-TiO2 and Pd/Cr-TiO2. Firstly, Cr3+ was in situ incorporated into the anatase crystalline lattice by the sol-gel method; then, Ag or Pd nanoparticles were deposited on Cr-TiO2 by chemical photoreduction. The scientific challenge addressed by the development of these composites was to analyse the recovery of Cr, to be employed in photocatalyst formulation and the enhancement of the TiO2 photocatalytic activity by addition of other noble metals. By extensive characterization, it was found that after TiO2 doping with chromium, the parameters of the crystal lattice slightly increased, due to the incorporation of Cr ions into the lattice. The TiO2 band gap decreased after Cr addition, but an increase in the optical absorptions towards the visible region after noble metals deposition was also observed, which was dependent of the Ag or Pd loading. Generally, it was observed that the noble metals type is a factor that strongly influenced the effectiveness of the photocatalysts concerning each substrate studied. Thus, by using Ag(0.1%)/Cr-TiO2, the complete elimination of E. coli from samples of water coming from a highly polluted river was achieved. Pd(0.5%)/Cr-TiO2 showed the highest efficiency in the elimination of S. cerevisiae from a lab prepared strain. On the other hand, the Pd(0.1%)/Cr-TiO2 sample shows the highest dye degradation rate, achieving 92% of TOC removal after 180 min.